Analysis Of Traffic Growth On The Pavement Design Life Of Kh. Ahmad Dahlan Pohjentrek Road, Pasuruan City, Using The Mdp Bina Marga 2024 Method - Rino Wahyu Pamungkas; Budi Witjaksana; Jaka Purnama (Journal of Social Science, 2025)
This study analyzes the impact of traffic growth on the pavement design life of KH. Ahmad Dahlan Pohjentrek Road in Pasuruan City using the Manual for Pavement Design (MDP) by Bina Marga 2024. The increasing volume of traffic, especially from heavy vehicles, has led to accelerated road deterioration and a significant reduction in the pavement's planned design life. The CESAL (Cumulative Equivalent Standard Axle Load) values exceeded the initial projections, reducing the planned lifespan from 10 years to 8 years. This finding highlights the critical need for regular evaluations of pavement thickness and the implementation of stricter monitoring systems for heavy vehicle loads. Advanced technologies, such as Weight-in-Motion (WIM) systems, can be instrumental in real-time vehicle load monitoring, thereby preventing further deterioration. Additionally, revising pavement designs to incorporate more robust materials and increasing layer thickness can enhance road durability. This study emphasizes the importance of adaptive and proactive road management strategies, including policy adjustments and routine maintenance programs, to ensure the longevity and functionality of critical infrastructure, particularly in regions experiencing rapid traffic growth. The findings serve as a reference for local governments and stakeholders in developing sustainable road management practices